2021
DOI: 10.1007/s13311-020-00976-6
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Modulates Behavioural and Gene Expression Alterations Induced by Spontaneous Cocaine Withdrawal

Abstract: The aim of this study was to evaluate the effects of cannabidiol (CBD) on the behavioural and gene expression changes in a new animal model of spontaneous cocaine withdrawal. For this purpose, male CD-1 mice were exposed to progressive increasing doses of cocaine for 12 days (15 to 60 mg/kg/day, i.p.), evaluating spontaneous cocaine withdrawal 6 h after the last cocaine administration. The effects of CBD (10, 20, and 40 mg/kg, i.p.) were evaluated on cocaine withdrawal-induced alterations in motor activity, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 61 publications
4
15
0
Order By: Relevance
“…In particular, 1 displayed strong interactions with the key residues D138 3.32 , Y139 3.33 , M142 3.36 , and V230 5. 43 . Compound 1 also stabilized specific motifs known to aid in receptor activation via π-stacking (YYY and PIF motif), hydrogen bonding (KEY and DRY motif), or water-mediated interactions (NPxxY motif) within the compound 1-inactive-state KOR complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, 1 displayed strong interactions with the key residues D138 3.32 , Y139 3.33 , M142 3.36 , and V230 5. 43 . Compound 1 also stabilized specific motifs known to aid in receptor activation via π-stacking (YYY and PIF motif), hydrogen bonding (KEY and DRY motif), or water-mediated interactions (NPxxY motif) within the compound 1-inactive-state KOR complex.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that spontaneous motor behaviors are indicative of cocaine withdrawal; 43 5C). Consistent with the behaviors of cocaine withdrawal, mice in the cocaine-exposed control group traveled significantly greater distances (p = 0.003; Figure 5A) at greater velocities (p = 0.004; Figure 5B), and demonstrated more frequent rearing behavior (p = 0.02; Figure 5C) than did saline-administered controls.…”
Section: Evaluation Of 1 On Spontaneous Motor Anxiety-like and Depres...mentioning
confidence: 96%
“…In different animal models of ethanol consumption (voluntary consumption, SA, and bingedrinking) the administration of CBD significantly reduced ethanol rewarding and the motivational actions that were associated with a reduction in the gene expression of TH in the VTA (Viudez-Martínez et al, 2018a;Viudez-Martinez et al, 2018b;Viudez-Martínez et al, 2020). Similarly, CBD significantly decreases TH in mice exposed to spontaneous cocaine withdrawal (Gasparyan et al, 2020). Nevertheless, in an animal model of spontaneous cannabinoid withdrawal CBD enhanced TH gene expression in the VTA (Navarrete et al, 2018).…”
Section: Cbd and Dopaminergic Systemmentioning
confidence: 96%
“…normalized motor and somatic signs disturbances and completely regulated anxiety-like behaviors induced by spontaneous cocaine withdrawal (progressive increasing doses of cocaine for 12 days, 15-60 mg/kg/day, i.p.). Furthermore, the administration of CBD blocked the increase of dopamine transporter (DAT) and TH gene expressions in the VTA of mice exposed to the cocaine withdrawal (Gasparyan et al, 2020).…”
Section: Cocaine Use Disordermentioning
confidence: 99%
“…We observed increased transcript levels of CB1Rs in the NAc, DS, and HPC whereas CB2R expression decreased significantly in the PFC and DS following cocaine self-administration. In a mouse model of spontaneous cocaine withdrawal, a decrease and increase were reported in the NAc for CB1R and CB2R transcripts, respectively [87]. Opposite patterns of protein expression were reported for CBRs in basal conditions in adolescent, compared to adult, rats (CB1R higher and CB2R lower) in both the PFC and HPC.…”
Section: Opposite Role Of Cb1rs and Cb2rs In Cocaine Adaptationsmentioning
confidence: 96%